Mitochondrial fatty acid synthesis is required for normal mitochondrial morphology and function in Trypanosoma brucei - Guler, Jennifer L. (2008)
Trypanosoma brucei use microsomal elongases for de novo synthesis of most of its fatty acids. In addition, this parasite utilizes an essential mitochondrial type II synthase for production of octanoate (a lipoic acid precursor) as well as longer fatty acids such as palmitate. Evidence from other organisms suggests that mitochondrially synthesized fatty acids are required for efficient respiration but the exact relationship remains unclear. In procyclic form trypanosomes, we also found that RNAi depletion of the mitochondrial acyl carrier protein, an important component of the fatty acid synthesis machinery, significantly reduces cytochrome-mediated respiration. This reduction was explained by RNAi-mediated inhibition of respiratory complexes II, III and IV, but not complex I. Other effects of RNAi, such as changes in mitochondrial morphology and alterations in membrane potential, raised the possibility of a change in mitochondrial membrane composition. Using mass spectrometry, we observed a decrease in total and mitochondrial phosphatidylinositol and mitochondrial phosphatidylethanolamine. Thus, we conclude that the mitochondrial synthase produces fatty acids needed for maintaining local phospholipid levels that are required for activity of respiratory complexes and preservation of mitochondrial morphology and function.